Higher Mortality Despite Early Antiretroviral Therapy in Human Immunodeficiency Virus and Hepatitis B Virus (HBV)–Coinfected Patients With High HBV Replication. (19th August 2017) - Kouamé, Gérard-Menan; Boyd, Anders; Moh, Raoul; Badje, Anani; Gabillard, Delphine; Ouattara, Eric; Ntakpe, Jean-Baptiste; Emième, Arlette; Maylin, Sarah; Chekaraou, Mariama Abdou; Eholié, Serge-Paul; Zoulim, Fabien; et al.
Abstract : HIV and hepatitis B virus (HBV) coinfected patients could benefit more from immediate versus deferred antiretroviral therapy (ART). However, in this randomized-control trial from sub-Saharan Africa, higher mortality was observed in coinfected patients with elevated HBV replication despite earlier ART. Abstract: Background: In human immunodeficiency virus (HIV)–infected patients, hepatitis B virus (HBV) coinfection increases the risk of disease progression. Tenofovir plus emtricitabine/lamivudine (TDF/XTC)–based antiretroviral therapy (ART), which suppresses HIV and HBV replication, has the potential for decreasing this risk. Here, we analyze the association between HBV replication, early ART, and mortality in West African adults. Methods: The Temprano randomized controlled trial assessed the benefits of immediately initiating vs deferring ART in HIV-infected adults with high CD4 counts. After trial completion, participants continued follow-up in a posttrial phase. We analyzed the association between HBV status, immediate ART, and mortality over the entire trial and posttrial follow-up using multivariable Cox proportional hazards regression. Results: A total of 2052 HIV-infected adults (median baseline CD4 count, 464 cells/μL) were followed for 9394 person-years. At baseline, 1862 (91%) were HIV monoinfected and 190 (9%) HIV/HBV coinfected. Of the latter, 135 (71%) had plasma HBV DNA <2000 IU/mL and 55 (29%) HBV DNA ≥2000 IU/mL. The 60-month probability of death was 11.8% (95% confidence interval [CI], 5.4%–24.5%) in coinfected patients with HBV DNA ≥2000 IU/mL; 4.4% (95% CI, 1.9%–10.4%) in coinfected patients with HBV DNA <2000 IU/mL; and 4.2% (95% CI, 3.3%–5.4%) in HIV-monoinfected patients. Adjusting for ART strategy (immediate vs deferred), the hazard ratio of death was 2.74 (95% CI, 1.26–5.97) in coinfected patients with HBV DNA ≥2000 IU/mL and 0.90 (95% CI, .36–2.24) in coinfected patients with HBV DNA <2000 IU/mL compared to HIV-monoinfected patients. There was no interaction between ART strategy and HBV status for mortality. Conclusions: African HIV/HBV-coinfected adults with high HBV replication remain at heightened risk of mortality in the early ART era. Further studies are needed to assess interventions combined with early ART to decrease mortality in this population. Clinical Trials Registration: NCT00495651